Perancangan Sistem Kanban untuk Mengurangi Keterlambatan Komponen Rear Spar - Niken Ayu Pramudita; Prasetio, Murman Dwi; Suryadhini, Pratya Poeri (APIC, 2023)
Kanban literally means a visual note that usually takes the form of a card placed in a rectangular vinyl envelope and containing part information sent from one process to the previous process. The application of kanban is believed to optimize the production process. In this study, the kanban system was designed to reduce delays in Rear Spar components at PT. XYZ, a manufacturing company that produces aircraft, such as NC212 aircraft. The Rear Spar component on NC212 aircraft is often delayed. The main cause of Rear Spar delays is the unclear information and material flow so that operators on the Fabrication Line do not know when parts must be in the Assembly Line so that there is no priority for part work and some parts are late to be delivered to the Assembly Line. The design of the kanban system is carried out using the Constant-Quantity Withdrawal System method which consists of four stages, namely: calculating the lead time, calculating the necessary number of parts during the lead time, calculating safety inventory, and calculating the number of kanban cards. After calculating the number of kanban cards, the number of Assembly Line kanban cards to the Assembly Store is one sheet of production kanban and one sheet of withdrawal kanban. As for the number of Assembly Store kanban cards to the Fabrication Line is one sheet of production kanban for each part. The design of the kanban system is continued with the design of the kanban card, kanban mechanism, and kanban post position. The results obtained after simulating the design results using the simulation scenario made by the author are that the part making process is reduced by 41 minutes.